Challenges in the mangalitsa sector – present and future - Pocsai, Krisztina (Acta Agraria Debreceniensis, 2013)
The Hungarian mangalitza pig sector has experienced numerous structural changes in the past few decades. The increased demand in the foreign markets for the mangalitza pork, changes in the domestic consumer perceptions have increase the number of sows and breeders. After the European Union’s accession started a significant growth in the sector, which was due to the target programme from the year of 2005 for the keeping of animals representing high genetic value, as the breed is indigenous. From 2008 continuous decline can be observed. The main reason for the decrease was the drastic growth of feed costs because of the drought damage in 2007, and the global economic crisis. Since 2010, a further period of supports has been in place, it extands the willingness to keep mangalitza pigs and the number of sows continuously increasing. On the basis of the average farm size (58 sows/farm) in 2011 it can be stated, that after our EU’s accession the medium-sized farms became stronger. To evaluate the geographic concentration of the mangalitza livestock it was analysed the data of sow number among the years of 2000 and 2011. The geographic concentration of mangalitza stock has a medium value over each year under the survey period, except the years of 2004–2007, when the values of Herfindahl-Hirschman index (HHI) have low degrees. Due to the subvention period of indigenous breeds it was established more mangalitza farms in different parts of Hungary. Despite of the growth since 2000, numerous problems are in the segment. The aim of the study is to find out the sectoral problems, which are completed with the objectives tree and draw up the main activities to solve the problems. After estimating the SWOT-matrix according to the methodology of the strategic analysis and the discussions with the secretary of National Association of Mangalitza Breeders is prepared the sectoral problem- and objectives tree. The core problem of the mangalitza sector is that the origin of mangalitza products are not certified in the domestic markets. The reason of it is that the breeders don’t request the certificates of fattening pigs, so it can appear not real mangalitza product on the markets as mangalitza. To solve the problems it is drawn up different suggestions in the objectives tree. This analysis is an useful tool for the decision makers in the mangalitza sector to evolve strategic plans on behalf of the efficient cooperations among chain actors.